Valley Splitting in a Silicon Quantum Device Platform - Miwa, J.; Warchkow, O.; Carter, Damien; Marks, Nigel; Mazzola, F.; Simmons, M.; Wells, J. (American Chemical Society, 2014)
By suppressing an undesirable surface Umklapp process, it is possible to resolve the two most occupied states (1Г and 2 Г) in a buried two-dimensional electron gas (2DEG) in silicon. The 2DEG exists because of an atomically sharp profile of phosphorus dopants which have been formed beneath the Si(001) surface (a δ -layer). The energy separation, or valley splitting, of the two most occupied bands has critical implications for the properties of δ -layer derived devices, yet until now, has not been directly measurable. Density functional theory (DFT) allows the 2DEG band structure to be calculated, but without experimental verification the size of the valley splitting has been unclear. Using a combination of direct spectroscopic measurements and DFT we show that the measured band structure is in good qualitative agreement with calculations and reveal a valley splitting of 132 ± 5 meV. We also report the effective mass and occupation of the 2DEG states and compare the dispersions and Fermi surface with DFT.